Applying the Discovery Learning Model to Enhance Students’ Learning Competence in Information and Communication Technology (ICT) Education - Oktavianus Turuna Gulo (Jurnal Pendidikan Vokasi Indonesia, 2025)
This study aims to improve students' understanding of the Computer Networks topic in the Information and Communication Technology (ICT) subject for Grade X at YAPIM Senior High School, Medan, through the application of the Discovery Learning model. The research method employed is Classroom Action Research (CAR), conducted over two cycles. Each cycle included planning, implementation, observation, and reflection phases. The results showed a significant improvement in students' comprehension, indicated by an increase in the average test scores from 58 in the first cycle to 83.8 in the second cycle. These findings suggest that the application of the Discovery Learning model is effective in enhancing students' understanding of Computer Networks material.